Menurunkan Ng Talc Depth Pada Produk Spark Plug di Line Final Assy PT XYZ Menggunakan Metode Plan Do Check Action - Rahmasari, Anggita; Rahayu, Siti; Windyatri, Hasyrani (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT XYZ is one of the companies engaged in manufacturing automotive components. In the production process in the final line of the assy, there are quite a lot of No Good (NG) products every month. The types of not good (NG) products discussed in this study are talc depth, insulator height, u-ring depth, and caulking height. The dominant percentage of No Good is 45.88% of the total No Good in the October-December 2023 period. This study aims to find out what types of No Good often occur in products, factors that cause No Good in products, provide No Good product repair solutions, and repair results using Plan Do Check Action (PDCA) and 5W+1H methods. By the PDCA method, it is hoped that quality improvement will continue, so that the quality will improve. The results of the analysis and improvement showed that there was a decrease in the percentage of No Good to 1.89% after improvements in the final line assy for the January-March 2024 period.